2015
DOI: 10.1002/col.22011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ceramic veneer thickness and cement shade on the CIELAB system after bonding—an in vitro study

Abstract: : In restoration dentistry clinicians need to control the effect of the ceramic thickness and cement shade to achieve successful colorimetric results when allceramic veneers are bonded. The purpose of this study was to evaluate the in vitro effects of cement color and the thickness of the final shade on porcelain discs. The study sample comprised 120 e.max Press HT A-2 ceramic discs of two thicknesses (60 of 1 mm thick and 60 of 0.5 mm thick). Three different lightnesses of Variolink Veneer cement were used (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(99 reference statements)
1
3
0
Order By: Relevance
“…The thickness of translucent metal-free restorations is an essential factor in achieving accurate color matching [48]. Various studies have reported that the color differences decrease when the thickness of the restoration is increased [11,17,49]. Similarly, in the present study, ∆E 00 values decreased when the thickness of the restoration was increased, except for the A1 cement groups.…”
Section: Discussionsupporting
confidence: 66%
“…The thickness of translucent metal-free restorations is an essential factor in achieving accurate color matching [48]. Various studies have reported that the color differences decrease when the thickness of the restoration is increased [11,17,49]. Similarly, in the present study, ∆E 00 values decreased when the thickness of the restoration was increased, except for the A1 cement groups.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, the intrinsic discoloration may be affected by the thickness of the ceramic and the color of the cementation area in the background ( 30 ). Ceramics with a greater thickness exhibit higher color stability ( 8,31 ). The color stability of dental materials should measure on a white background according to ISO standardization ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that white opaque cements provide masking ability when the silver-palladium alloy is used and it results in desirable shade of final restorations of machinable lithium disilicate. In an in vitro study by Montero et al [8] color stability of e.max ceramic was evaluated after bonding with various shades of cements. They showed that cement color is the main factor predicting the final color.…”
Section: Cement Thicknessmentioning
confidence: 99%